(3eNJUQ hLhg GdbQGAGJ hGdGYJdGd Ydi GdQhGjGJs - (3CMeO Hf YeGQ Hf CHj GdYHGS GdegOhj, CHh GdYHGS,J (B440 (3g` s
(3ChdgG (B:s
(3CeG HYO MeOkG ddg HLejY eMGeOg bO SCdfi SGFdhf cJGHkG eNJUQkG ai TQM hLhg GdbQGAGJ s
(3BNQgG (B:s
(3hGdQaY Ydi Cf GeQCJg QaY GdGHJOGA hMeGdI NHQg hGScGf GdgGA ai dgjH haJMgG GfJgi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3hQO GdYfhGf GdCUdi ai cTa GdXfhf HQbe (B2 / 2040 s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs